Avaliação do impacto do diabetes gestacional na próstata de ratos neonatos e pré-púberes - Peixoto, Luiz Felipe Fernandes (2023)
Gestational diabetes mellitus (GD) is the most commom medical complication during prenancy. It creates a hyperglycemic environment and impacts offspring development, increasing the risk of long-term complications, including obesity, impaired glucose metabolism and cardiovascular disease. The impact of GD on the prostate of adult offspring is already described, however it is not known whether these effects are due only to the maternal condition or if the offspring develops them throughout life. This investigation evaluated the prostate of the neonatal and prebubertal offspring of diabetic rats. Diabetes was induced in pregnant Wistar rats with streptozotocin (50mg/kg, i.p.) and the 7 or 30-days old pups from healthy (PC7, PC30) or diabetic (PD7, PD30) rats had the prostate evaluated. GD reduced body weight in PD7 and PD30 and the prostate weight in PD30. The prostate branching was not affected but a reduction in apoptotic levels was associated to impaired acinar bud canalization in neonates. Additionally, GD reduced ERK1/2 phosphorylation, cell proliferation and collagen quantity in PD7. In PD30, GD led to a reduction in the secretory epithelium and stroma but increased the luminal área. Moreover, smooth muscle cells and collagen was decreased in these prepubertal pups which may impair stromal normal development. These data indicate that GD inactivates an important cell proliferation signaling in the prostate in the first postnatal days which is restored in prebubertal period but it was not sufficient to avoid epithelial atrophy. This effect of GD on epithelium and stroma development can impact the reproductive capacity of the offspring at adult life.